2010
DOI: 10.1089/sur.2009.046
|View full text |Cite
|
Sign up to set email alerts
|

Empiric, Broad-Spectrum Antibiotic Therapy with an Aggressive De-Escalation Strategy Does Not Induce Gram-Negative Pathogen Resistance in Ventilator-Associated Pneumonia

Abstract: In our SICU, early, empiric broad-spectrum VAP therapy followed by de-escalation to pathogen-specific agents did not alter antimicrobial resistance and is a valid practice. Further, our compliance with de-escalation practices was higher than published rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Delaying treatment and failing to cover patients' causative pathogens are both associated with higher mortality rates Conversely, broader coverage and longer treatment courses increase the risks of adverse drug effects, C. difficile infections, and antimicrobial resistance [191,192]. The generally recommended compromise is to pair early and aggressive treatment with early and aggressive de-escalation (see section XXIII) [68,84,120,[193][194][195][196][197].…”
Section: Rationale For the Recommendationsmentioning
confidence: 99%
“…Delaying treatment and failing to cover patients' causative pathogens are both associated with higher mortality rates Conversely, broader coverage and longer treatment courses increase the risks of adverse drug effects, C. difficile infections, and antimicrobial resistance [191,192]. The generally recommended compromise is to pair early and aggressive treatment with early and aggressive de-escalation (see section XXIII) [68,84,120,[193][194][195][196][197].…”
Section: Rationale For the Recommendationsmentioning
confidence: 99%
“…The guidelines suggest that therapy can be narrowed to a single agent if lower respiratory tract cultures do not demonstrate resistant pathogens. It has been shown that this approach of deescalation contributes to the preservation of antimicrobial susceptibilities (8,110).…”
Section: Hospital-acquired Pneumoniamentioning
confidence: 99%
“…A collegiate body, including intensive care specialists, clinical microbiologists and infectious diseases specialists, performed daily reviews of antibiotic treatments according to clinical evolution and microbiological results. De-escalation was carried out in accordance with international definitions [14,15].…”
Section: Methodsmentioning
confidence: 99%